1972
DOI: 10.1111/j.1365-3180.1972.tb01214.x
|View full text |Cite
|
Sign up to set email alerts
|

SHOOT ZONE UPTAKE OF SOIL‐APPLIED HERBICIDES IN PISUM SATIVUM L.

Abstract: Summary. The effects of localized herbicide placement at different internodes of pea (Pisum sativum L. cv. Alaska) shoots below the soil surface after plant emergence were studied by removing the soil from around the shoots and replacing with herbicide‐treated soil. The first internode proved insensitive to linuron, diuron, atrazine and simazine at 4·5 kg/ha, while treatment of the second and third internodes markedly reduced plant growth 4–6 days after treatment. Separate exposure of the first internode alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1975
1975
1985
1985

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…In this study the greatest reduction in plant growth occurred when the herbicide was present in soil at the upper part of the emerging shoot. Similar differences in sensitivity of different parts of the pea shoot were found by Prendeville (1968) and by O'Brien & Prendeville (1972). They have shown that, after plant emergence, pea is not susceptible from exposure of the first internode of its shoot below the soil surface to diuron, linuron, atrazine and simazine.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…In this study the greatest reduction in plant growth occurred when the herbicide was present in soil at the upper part of the emerging shoot. Similar differences in sensitivity of different parts of the pea shoot were found by Prendeville (1968) and by O'Brien & Prendeville (1972). They have shown that, after plant emergence, pea is not susceptible from exposure of the first internode of its shoot below the soil surface to diuron, linuron, atrazine and simazine.…”
Section: Discussionsupporting
confidence: 69%
“…Movement of these herbicides from the soil via the ground parts of the plants to the site of herbicidal action is essential for phytotoxicity performance. O'Brien & Prendeville (1972) explain the insensitivity of pea from exposure of its lower internode as a result of the lower shoot being more mature with fuller epidermal and cuticular development. In these experiments pea seedlings were exposed to the herbicides during the germination and emergence processes, and therefore differences in maturity of the different parts of the shoot cannot account for differential susceptibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The above data also indicate that the differential sensitivity of the shoot internodes to soil-applied photosynthesis-inhibiting herbicides, which was evident in the shoot of pea (O'Brien & Prendeville, 1972), is not a characteristic of all legume species. Table 4 Effect of placement of •*C-atrazine (mixed with unlabelled atrazine up to 0-25 mg/kg dry sand) on accumulation of "'C within the plant when applied with and without trifluralin (1 mg/kg dry sand) to the shoot of vetch below the soil surface after emergence ' Each treatment received 0-5 /(Ci of isotope (specific activity 10'2 /iCi/mg)…”
Section: Resultsmentioning
confidence: 78%
“…In pea, treatment of the first internode with simazine, atrazine, linuron and diuron did not affect plant growth, whereas treatment of the second and third internodes markedly reduced growth. The more mature first internode allowed for less atrazine uptake than the less mature second internode (O'Brien & Prendeville, 1972).…”
Section: Introductionmentioning
confidence: 93%